Modulation of Intestinal Microbiome Prevents Intestinal Ischemic Injury - Bertacco, Alessandra; Dehner, Carina A.; Caturegli, Giorgio; D'Amico, Francesco; Morotti, Raffaella; Rodriguez, Manuel I.; Mulligan, David C.; Kriegel, Martin A.; Geibel, John P. (Frontiers in Physiology, 2017)
Background: Butyrate protects against ischemic injury to the small intestine by reducing inflammation and maintaining the structure of the intestinal barrier, but is expensive, short-lived, and cannot be administered easily due to its odor. Lactate, both economical and more palatable, can be converted into butyrate by the intestinal microbiome. This study aimed to assess in a rat model whether lactate perfusion can also protect against intestinal ischemia. Materials and Methods: Rat intestinal segments were loaded in an in vitro bowel perfusion device, and water absorption or secretion was assessed based on fluorescence of FITC-inulin, a fluorescent marker bound to a biologically inert sugar. Change in FITC concentration was used as a measure of ischemic injury, given the tendency of ischemic cells to retain water. Morphological changes in the intestinal wall were also assessed by hematoxylin and eosin stained sections at light level microscopy. Comparisons between the data sets were paired Student t-tests or ANOVA with p < 0.05 performed on GraphPad. Results: Lactate administration resulted in a protective effect against intestinal ischemia of similar magnitude to that observed with butyrate. Both exhibited approximately 1.5 times the secretion exhibited by control sections (p=0.03). Perfusion with lactate and methoxyacetate, a specific inhibitor of lactate-butyrate conversion, abolished this effect (p=0.09). Antibiotic treatment also eliminated this effect, rendering lactate-perfused sections similar to control sections (p=0.72). Perfusion with butyrate and methoxyacetate did not eliminate the observed increased secretion, which indicates that ischemic protection was mediated by microbial conversion of lactate to butyrate (p=0.71). Conclusions: Lactate’s protective effect against intestinal ischemia due to microbial conversion to butyrate suggests possible applications in the transplant setting for reducing ischemic injury and ameliorating intestinal preservation during transport.